(untitled) (Confluenţe Bibliologice, 2018)
In the article is described the anniversary exhibition dedicated to the plastic artist and art critic Ada Zevin and exposed in the reading room „Psycho-pedagogical, natural, real. Arts „of the USARB Scientific Library.